Physics in D]= 4 : proceedings of the Theoretical Advanced Study Institute in Elementary Particle Physics : TASI 2004 : Boulder, CO, USA, 6 June-2 July 2004 - Terning, John, 1962-; Wagner, Carlos E. M.; Zeppenfeld, Dieter, 1956- (World Scientific, 2006)
This book contains write-ups of lectures from a summer school for advanced graduate students in elementary particle physics. In the first lecture, Scott Willenbrock gives an overview of the standard model of particle physics. This is followed by reviews of specific areas of standard model physics : precision electroweak analysis by James Wells, quantum chromodynamics and jets by George Sterman, and heavy quark effective field by Matthias Neubert. Developments in neutrino physics are discussed by Andre de Gouvea and the theory behind the Higgs boson is addressed by Laura Reina. Collider phenomenology from both experimental and theoretical perspectives are highlighted by Heidi Schellman and Tao Han. A brief survey of dynamical electroweak symmetry breaking is provided by R Sekhar Chivukula and Elizabeth H Simmons. Martin Schmaltz covers the recent proposals for "little" Higgs theories. Markus Luty describes what is needed to make supersymmetric theories realistic by breaking supersymmetry. There is an entire series of lectures by Raman Sundrum, Graham Kribs, and Csaba Csaki on extra dimensions. Finally, Keith Olive completes the book with a review of astrophysics